Parental involvement and achievement motivation: association with students' achievement in vocational colleges, Malaysia - Omar, Rosmaria; Ahmad, Nor Aniza; Hassan, Siti Aishah; Roslan, Samsilah (Human Resource Management Academic Research Society, 2017)
This study to identify the relationships between parental involvement and achievement motivation with an objective measure of the students’ achievement through students’ perception in vocational colleges, Malaysia. The study also examined the mediating effects of achievement motivation with students’ achievement and moderating role of gender for the link between parental involvement, achievement motivation and students’ achievement. Three hundred and sixty students (106 girls and 264 boys) were selected at thirteen vocational colleges students’ all around Malaysia. Our results showed that parental involvement were positively related with achievement motivation and students’ achievement which in turns achievement motivation also related to students’ achievement. There is full mediation effects between achievement motivation and parental involvement with students’ achievement. While gender were moderately correlated between achievement motivation and students’ achievement. The findings contribute to understanding commonly reported the relationships between parental involvement and achievement motivation elements with students’ achievement among the students in vocational colleges.